The evolving female : a life-history perspective - Morbeck, Mary Ellen, 1945-; Galloway, Alison, 1953-; Zihlman, Adrienne L. (Princeton University Press, 1997)
A human female is born, lives her life, and dies within the space of a few decades, but the shape of her life has been strongly influenced by 50 million years of primate evolution and more than 100 million years of mammalian evolution. How the individual female plays out the stages of her life--from infancy, through the reproductive period, to old age--and how these stages have been formed by a long evolutionary process, is the theme of this collection. Written by leading scholars in fields ranging from evolutionary biology to cultural anthropology, these essays together examine what it means to be female, integrating the life histories of marine mammals, monkeys, apes, and humans. The result is a fascinating inquiry into the similarities among the ways females of different species balance the need for survival with their role in reproduction and mothering. The Evolving Female offers an outlook integrating life history with an intimate examination of female life paths. Behavior, anatomy and physiology, growth and development, cultural identity of women, the individual, and the society are among the topics investigated. In addition to the editors, the contributors are Linda Fedigan, Kathryn Ono, Joanne Reiter, Barbara Smuts, Mariko Hiraiwa-Hasegawa, Mary McDonald Pavelka, Caroline Pond, Robin McFarland, Silvana Borgognini Tarli and Elena Repetto, Gilda Morelli, Patricia Draper, Catherine Panter-Brick, Virginia J. Vitzthum, Alison Jolly, and Beverly McLeod.
Keywords: Human evolution.; Women -- Evolution.; Females -- Physiology.; Women's studies -- Biographical methods.; Êtres humains -- Évolution.; Femmes -- Évolution.; Femelles -- Physiologie.; Études sur les femmes -- Histoires de vie.; SOCIAL SCIENCE -- Anthropology -- Physical.; SCIENCE -- Life Sciences -- Evolution.; Homme -- Evolution.; Femmes -- Evolution.; Etudes sur les femmes -- Methode biographique.; Females -- Physiology; Human evolution; Women -- Evolution; Women's studies -- Biographical methods; Säugetiere; Weibchen; Evolution; Frau; Vrouwen.; Evolutie.; Vergelijkende fysiologie.; Homme -- Origines.